Crizotinib in anaplastic lymphoma kinase-positive anaplastic large cell lymphoma in the setting of renal insufficiency: a case report. (December 2016) - Kothari, Shalin; Ud-Din, Najam; Lisi, Michele; Coyle, Thomas
Abstract Background In vitro studies confirmed cytoreductive anti-tumor activity of crizotinib in experimental models of anaplastic large cell lymphoma in 2007. One case series and a few case reports describe the use of crizotinib in relapsed or refractory anaplastic lymphoma kinase-positive anaplastic large cell lymphoma. Even though data are limited regarding the dose of crizotinib in renal insufficiency, our case was successfully treated with a lower dose of crizotinib. Case presentation We report the case of a 48-year-old white man who had progressive disease after three prior cycles of cyclophosphamide, doxorubicin, vincristine and prednisone and three cycles of ifosfamide, carboplatin, and etoposide, and was not a candidate for high-dose chemotherapy and transplant due to poor performance status and renal insufficiency; he had a complete and durable response to single agent crizotinib. Crizotinib was given at a reduced dose (250 mg once daily) due to his renal insufficiency. He has been in complete remission for more than 2 years. Conclusions Our experience confirms the activity of crizotinib in this disease; it suggests that long-term treatment with crizotinib is a reasonable option in patients who are not candidates for more aggressive therapy and indicates that crizotinib can be used successfully at reduced doses in patients with pre-existing renal insufficiency. The role and timing of crizotinib in anaplastic lymphoma kinase-positive anaplastic large cell lymphoma is unclear, but the current literature that we review here provides promising results that may lead to studies of crizotinib earlier in the course of disease.